Effect of smoking cessation in saliva compounds by FTIR spectroscopy - Rodrigues, Laís Morandini [UNESP] (2017)
Introduction Smoking is currently considered one of the biggest risk factors for the development of various diseases and early death. Fourier transform infrared (FTIR) spectroscopy is a valuable tool for analysis of biofluids such as saliva and is considered useful for diagnostic purposes. The aim of this study was to evaluate the effect of smoking cessation on saliva composition by FTIR spectroscopy. Methods We analyzed the saliva of participants in two groups: a smoker group made up of 10 chronic smokers and a former smoker group made up of 10 individuals who had stopped smoking. Members of both groups had similar smoking history. Results The results showed few differences in spectral intensity between the groups; however, spectral peaks were slightly increased in the group of smokers in the bands for DNA, indicating modification of its content or cell necrosis. They were also increased for the mannose-6-phosphatase molecule, which is expressed in prostate and breast carcinomas. In the former smoker group, the peak of thyociante was decreased and the band referring to collagen increased in intensity, which indicates a better tissue regeneration capacity. Conclusion Considering these results and the fact that tobacco intake was similar between the groups, it can be concluded that there was recovery of tissue regeneration capacity with smoking cessation during the study period, although the effects found in smokers persisted in the bodies of those who had given up smoking.